La théorie de Heckscher-Ohlin et la localisation des industries manufacturières canadiennes : présentation de quelques résultats empiriques - Boucher, Michel (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractThis paper applies the Heckscher-Ohlin hypothesis to the location of regional manufacturing industries in Canada. The empirical results demonstrate with strong evidence the first hypothesis that Quebec and Ontario enjoy different locational characteristics because of their relative factor endowments. More precisely, firms operating in Quebec adopt labor-intensive production process relatively to those located in Ontario which choose a capital-intensive production technique. The statistical results of the second hypothesis confirm sufficiently that both provinces increased their specialization in industries when they have a relative increasing comparative advantage respectively labor-intensive industries for Quebec and capital-intensive industries for Ontario. Finally, those hypotheses are confirmed not only for the twenty two-digit manufacturing industries of the Standard Industrial Classification (SIC), but also for thirty-one three-digit manufacturing industries.